2015
DOI: 10.1002/eat.22420
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism due to Hashimoto's thyroiditis masked by anorexia nervosa

Abstract: Anorexia nervosa (AN) is typically associated with altered thyroid function tests, notably a low total and free T3 , and lower, but within normal range, free T4 and TSH. A 16-year-old girl with a four-year history of AN presented with elevated TSH that fluctuated with changes in weight. TSH was within normal limits (1.7-3.64 mIU/L) following periods of weight loss and elevated with weight gain (5.9-21.66 mIU/L). Antithyroperoxidase antibodies were markedly elevated, suggesting chronic Hashimoto's thyroiditis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Our study observed decreased TSH and fT4 levels in patients with AN (but still in the normal range defined for normal BMI subjects) that did not increase even after treatment (Table ). Our results are in accordance with previous studies that have described altered thyroid function in AN patients. , Endocrine dysregulation is considered to be an adaptation to long-term starvation followed by the slowdown of energy metabolism . As expected, these extensive hormonal changes were also projected in metabolism.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study observed decreased TSH and fT4 levels in patients with AN (but still in the normal range defined for normal BMI subjects) that did not increase even after treatment (Table ). Our results are in accordance with previous studies that have described altered thyroid function in AN patients. , Endocrine dysregulation is considered to be an adaptation to long-term starvation followed by the slowdown of energy metabolism . As expected, these extensive hormonal changes were also projected in metabolism.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in accordance with previous studies that have described altered thyroid function in AN patients. 19,20 Endocrine dysregulation is considered to be an adaptation to long-term starvation followed by the slowdown of energy metabolism. 21 As expected, these extensive hormonal changes were also projected in metabolism.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The elevated TSH that would be expected in Hashimoto's thyroiditis was blunted by weight loss associated with Anxiety Neurosis was reported early (9). Consequences of untreated subclinical hypothyroidism are dyslipidemia, coronary artery disease, CHF, cognitive dysfunction and neuropsychiatric symptoms and progression to overt symptomatic hypothyroidism.…”
Section: Resultsmentioning
confidence: 99%
“…Review of the literature for the association of Hashimoto thyroiditis with EDs revealed only one recently published case report of a 16-year-old girl with a 4-year history of AN whose TSH levels had increased in response to weight gain and shown a decrease with weight loss. This unexpected pattern of TSH and markedly elevated levels of antithyroperoxidase antibodies suggested Hashimoto thyroiditis ( 17 ). The association between body weight and TSH levels observed in this case report was also present in our patient.…”
Section: Discussionmentioning
confidence: 98%